Under Construction: Urban Practices of Terrain Vague in Upper Silesia - Petri, Jakub (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
The Silesian conurbation consists of large amounts of terrains of uncertain status. Empty areas left after closed coal mines, ironworks, decommissioned working-class recreation zones or simply SLOAPS (Spaces Left Over After Planning) tend to be increasingly noticed by Silesian citizens nowadays and the experience of terrain vagues has become an important factor shaping their daily routine. The article covers the one, chosen distinct Silesian terrain vague location: the landscape park Żabie Doły (situated in municipalities of Bytom – Chorzow – Siemianowice Śląskie) in a quest to investigate the „unintentional landscape” as a place of different independent urban practices, undertaken by inhabitants. Terrain vague is being presented as an opportunity rather than a burden for a modern urban planning.